Prácticas de alimentación de los padres y conductas alimentarias en niños : ¿Existe información suficiente para el abordaje de los problemas de alimentación? (2014)
ABSTRACT: The infant feeding problems increase despite the efforts of government institutions to monitor nutritional health indicators and education campaigns that provide information. This article seeks to review information available about the management of infant feeding problems. The first part shows the status of infant feeding problems and points out the consequences of the lack of information for its approach. The second analyzes the consequences of feeding practices of parents on feeding behaviors of children and the possible repercussions in adulthood. We conclude that should be investigated psychological, social and cultural aspects of feeding at children context.